Effect of technology-aided training on physiological and psychological sports performance: Moderation analysis of sport involvement - Yung-Chang Yu; Chen-Yueh Chen; Wen-Cheng Chen; Yen-Kuang Lin; Shu-Cheng Lu (PLoS ONE, 2025)
This study investigates the impact of technology-assisted sports training on the physiological and psychological performance of recreational exercisers (non-athletes), with particular attention to the moderating role of sport involvement (SI). A quasi-experimental design was employed, with 48 participants randomly assigned to either an experimental group (technology-assisted training) or a control group (traditional coaching) for an eight-week training program. Performance measures included exercise self-efficacy (ESE) and squat speed (SS). Data were analyzed using ANCOVA and linear mixed models. The results showed that technology-assisted training significantly improved SS (p = 0.026), but had no significant effect on ESE (p = 0.905). Furthermore, SI moderated the relationship between training method and ESE: participants with low SI demonstrated significant improvements in ESE under traditional coaching (p = 0.006), whereas those with high SI showed no significant differences between training methods. These findings suggest that while sports technology can enhance physical performance, it does not necessarily improve exercise self-efficacy. For individuals with low sport involvement, traditional coaching remains essential, highlighting the importance of combining technology with interpersonal interaction. Future training strategies should be customized according to participants’ levels of sport involvement to optimize both performance and psychological motivation, thereby promoting broader health engagement and exercise participation.